Environmental fate of nanoparticles: physical chemical and biological aspects – a few snapshots. (7th February 2012) - Masion, Armand; Auffan, Mélanie; Labille, Jérôme; Botta, Céline; Solovitch, Natalia; Rose, Jérôme; Bottero, Jean–Yves
The environmental risk that nanomaterials can undergo is a major problem, which could prevent the commercial development of nanoproducts, especially in technology domains corresponding to large distribution: cosmetics, composite materials, civil engineering materials and leisure materials. The risk assessment is based on a complex approach, which implies the knowledge of the degradation mechanisms of the nanoproducts in aquatic media (kinetics and chemical change), the quantities that are distributed in the different ecosystem compartments and the biological effects on various targets (bacterial micro–organisms, primary and secondary predators). The paper aims at showing the unique surface properties of nanomaterials and especially when the size is decreasing largely less than 100 nm, the stability and the eventual degradation of intermediate nanomaterials, e.g., some composites used in sunscreens. The biological effects of the nanomaterials depends on their unique properties and especially the large surface tension as the size decreases, the defects within the bulk and on the surface at the origin of the production of ROS. The molecular mechanisms underlying the toxicity are described especially in terms of oxidation–reduction reactions owing to surface reactivity, surface atoms dissolution, oxidative dissolution and dissolution.